2017
DOI: 10.1021/acs.energyfuels.6b02460
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Molecular Hydrogen Release Mechanism during Low-Temperature Oxidation of Coal

Abstract: Although H2 gas is used in coal mines as an important indicator to reflect the state of coal spontaneous combustion, the gas production of H2 at low temperature has been scarcely reported in the literature. In this paper, the modes and release mechanism of molecular hydrogen were investigated for three different coal ranks below 200 °C. Batch reactor tests were performed in combination with chromatographic analysis of the coal oxidation process. The experimental results showed that molecular hydrogen release m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…In addition, a peak from aldehyde markedly became larger after low-temperature oxidation. It has been reported that the aldehyde group is a functional group that produces not only CO 2 but also H 2 by its oxidation reaction (Wang et al, 2017). This fact is consistent with the H 2 emissions observed in the low-temperature oxidation of coal Q shown in Fig.…”
Section: Comparison Of Ftir Spectra Before and After Oxygen Chemisorpsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, a peak from aldehyde markedly became larger after low-temperature oxidation. It has been reported that the aldehyde group is a functional group that produces not only CO 2 but also H 2 by its oxidation reaction (Wang et al, 2017). This fact is consistent with the H 2 emissions observed in the low-temperature oxidation of coal Q shown in Fig.…”
Section: Comparison Of Ftir Spectra Before and After Oxygen Chemisorpsupporting
confidence: 88%
“…The weight reduction of the coal was almost consistent with the total mass of C and H contained in the emitted gaseous compounds. H 2 emissions in the low-temperature oxidation process of coal was reported by Wang et al (2017), in which the amount of H 2 emissions from sub-bituminous coal was greater than that from bituminous coal at temperatures higher than 373 K.…”
Section: Monitoring Of Gaseous Emissions During Low-temperature Oxidamentioning
confidence: 85%
“…The number, sub-peak position, peak width, and their variation ranges were assigned as in Table A1. These values were obtained from previous FTIR analysis of coal and biomass [49,[63][64][65][66][67][68][69][70], and were used to perform peak deconvolution. The band assignment in the OH-stretching region and the nine bands in the oxygen-containing region (anhydride, ester, aldehydes, carboxyl groups, conjugated carbonyl groups, etc.)…”
Section: Liquid Membrane-ftirmentioning
confidence: 99%
“…Appendix A Table A1. Peak assignments of IR spectra of the oxygen-containing groups in this study [49,[63][64][65][66][67][68][69][70].…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…As an organic macromolecular material, coal contains many active components. During the process of coal reacting with O 2 and its subsequent heating, functional groups, such as the ketone group, quinone group, and aldehyde group, are activated and are part of the reaction to produce CO [2]. CO is usually generated in an exponential manner with any increase of temperature [3,4].…”
Section: Introductionmentioning
confidence: 99%